Calculation Initial Craked Reinforced Concrete Highbeams - Averlingis, Edvinas; Šleževičius, Kazys; Roličius, Jonas (Jaunųjų mokslininkų darbai, 2017)
Calculation of various reinforced concrete highbeams at elastic stage using the method of final differences was carried out. Estimated zones of initial cracks were compared to cracks in experimental highbeams. Assumptions for calculating alligator highbeams are presented in this article. This method is to be applied at the initial stage of cracking before appearance of diagonal cracks. Using this method one is able to estimate the development of cracks, their location and investigate another particular crack. Calculation points out redistribution of the most unwanted tensioning. Assumptions can be made more precise by comparing the results of calculation with the experimental data. Reinforced concrete beams are affected by concentrated force in one third of openings and they rest on extreme points. First vertical cracks appear in the middle of the tensile zone. Increasing load causes appearance of diagonal cracks. Their development is more intensive than that of vertical cracks. Rupture is more likely to appear in a diagonal cross-section. Calculation shows that theoretical loads are higher than experimental data. It is particularly obvious in cases when the relation between the height of the beam and the opening is higher than 0,5. Calculation of theoretical loads is based on maximum tensile stress of an elastic body in a diagonal cross-section. Stresses are calculated using the method of a net. To avoid discrepancy an experimental theoretical equation is suggested, which allows us to make the maximum of main stresses more precise. Another equation is suggested in order to calculate the collapsing shear force in diagonal cross-sections. This equation takes into account bar reinforcing in cases of cross reinforce dimensions of a cross-section.